The Influence of Product Quality, Online Promotion and Price Perception on Buying Interest in Kopi Kenangan at Epicentrum Mall - Yogi Alfaizi; Resti Hardini; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to determine the Effect of Product Quality, Online Promotion, and Price Perception on Consumer Buying Interest in Kenangan Coffee at Epicentrum Mall. This study used quantitative research methods. Data for this study was collected through primary data using questionnaires distributed to 100 respondents who had purchased at Kopi Kenangan using the purposive sampling method. Purposive sampling techniques are used to ensure that samples match the conditions or criteria required in this study. The data used in this study were mainly collected through the dissemination of questionnaires. Data analysis was performed using IBM SPSS 23 software. The results, after analysis through data processing, concluded that product quality, online promotion, and price perception had a positive and significant impact on repeat purchase intent. Previously, questionnaire items have been tested for validity and reliability.Product Quality